Pelatihan Pembuatan Minyak Dedak (Rice Bran Oil) Dari Limbah Dedak Padi (Oryza Sativa) Sebagai Minyak Goreng Di Kelurahan Ulu Gedong Kecamatan Danau Teluk Kota Jambi - Minarni, Minarni; Listyarini, Diah; Muslim, Fachruddiansyah; Putra Fendika, Chery (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
This research aims to provide training to the community in Ulu Gedong Village, Danau Teluk Subdistrict, Jambi City, regarding the production of rice bran oil from rice bran waste (Oryza Sativa) as a healthier alternative to cooking oil. The formulation of the problem was the extent to which the training was effective in improving the community's understanding and skills in the bran oil production process as well as its impact on reducing rice bran waste. The research method used involved a series of practical training, observations, and interviews with trainees. The results showed that the training was successful in improving participants' knowledge and skills in producing bran oil from rice bran waste. In addition, the use of the resulting bran oil has helped to reduce agricultural waste and provide a healthier alternative to cooking oil. This has the potential to have a positive impact on community welfare and promote more sustainable agricultural practices.